Penerapan Algoritma Nearest Neighbour untuk Menyelesaikan Travelling Salesman Problem - Imam Sutoyo (Paradigma, 2018)
Traveling Salesman Problem (TSP) is a problem that has gained much attention from researchers in the field of computer science and mathematics. Many algorithms have been introduced to solve this TSP problem. The solution to be obtained is the optimal solution in the sense of getting the shortest route that can be used to visit all points once only then back to the starting point of the journey. This paper discusses the application of one of the algorithms to obtain solutions for TSP problems, ie Nearest Neighbors (NN) algorithm. The application of the NN algorithm to solve TSP problems proved to be efficient even though there is no guarantee that the solution provided is the most optimal solution.